Caracterização da óptica para a aprendizagem da física moderna e contemporânea na formação do professor de física - Paredes, Iris Naile Materán (2023)
Current changes require educational systems to take a critical position and move forward. Universities must remain at the forefront of scientific and technological changes. Teacher education programs urgently need to reform themselves to meet the demands of a constantly changing world, but also to produce new contexts. The way this task is faced requires a new way of thinking and producing knowledge. In this scenario, the general objective of this research was to characterize, through qualitative investigation, the contributions of optics to the learning of modern and contemporary physics from the epistemological approach of Bachelard, in the teacher education of physics at the Federal University of Uberlândia. Bachelardian ideas of epistemological obstacles, epistemological ruptures, error, and historical recurrence are analyzed, taking as a guiding thread the evolution of the concept of light in the history of physics, particularly in optics. The aim is to understand how the contents of the optics discipline (in this case, Physics IV) contribute to facilitating the learning of concepts in modern and contemporary physics. To achieve the research objectives, a study was conducted with teachers and students in the physics teacher education program to uncover their understanding of this relationship. Among the most important findings of the research, it is evident that those involved in the educational process of physics teacher education recognize the importance of optics ideas for constructing learning in modern physics. However, optics, along with the history of physics, remains as an appendix in the development of various physics contents. Therefore, it is considered important to empower teachers to integrate Bachelardian epistemology as a guiding element for reflection and active knowledge construction in conjunction with physics content.